Cytotoxic Effects and Anti-Angiogenesis Potential of Pistachio (Pistacia vera L.) Hulls against MCF-7 Human Breast Cancer Cells - Seifaddinipour, Maryam; Farghadani, Reyhaneh; Namvar, Farideh; Mohamad, Jamaludin; Abdul Kadir, Habsah (MDPI, 2018)
Pistachio (Pistacia vera L.) hulls (PVLH) represents a significant by-product of industrial pistachio processing that contains high amounta of phenolic and flavonoid compounds known to act as antioxidants. The current study was designed to evaluate the anti-tumor and anti-angiogenic potentials of PVLH extracts. The cytotoxic effects of hexane, ethyl acetate, methanol, and water PVLH extracts toward human colon cancer (HT-29 and HCT-116), breast adenocarcinoma (MCF-7), lung adenocarcinoma (H23), liver hepatocellular carcinoma (HepG2), cervical cancer (Ca Ski), and normal fibroblast (BJ-5ta) cells were assessed using a MTT cell viability assay. Apoptosis induction was evaluated through the different nuclear staining assays and confirmed by flow cytometry analysis. Anti-angiogenic activities were also determined using chorioallantoic membrane (CAM) assay. PVLH ethyl acetate extracts (PVLH-EAE) demonstrated a suppressive effect with an IC50 value of 21.20 ± 1.35, 23.00 ± 1.2 and 25.15 ± 1.85 µg/mL against MCF-7, HT-29 and HCT-116, respectively, after 72 h of treatment. Morphological assessment and flow cytometry analysis showed the potential of PVLH-EAE to induce apoptosis. PVLH-EAE at the highest concentration demonstrated significant inhibition of angiogenesis as comparing with control group. Also the expression of Bax increased and the expression of Bcl-2 decreased in treated MCF-7 cells. Thus, the apoptosis induction and angiogenesis potential of PVLH-EAE make it to be the most suitable for further cancer research study to deal with selective antitumor active substances to human cancers especially breast cancer.